METHODS OF SELECTING RADIOLACTION DEVICES FOR GAS CARS - Mirzayev, Bahodir; Zulpukarova, Guldonakhon (Techscience uz - Topical Issues of Technical Sciences, 2025)
This article considers the issues of improving safety and automation of technical control in the operation of gas-cylinder vehicles. A methodology based on RFID technology has been developed to enhance identification, technical condition monitoring, and service life control of gas cylinders. Based on laboratory and operational experiments, RFID tags were evaluated in terms of reading distance, signal stability, temperature, and humidity resistance. A multi-criteria mathematical model was applied to select optimal RFID tags, and their practical applicability in real operating conditions was confirmed.